2006
DOI: 10.1016/j.ejphar.2005.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and neurobiological effects of the enkephalinase inhibitor RB101 relative to its antidepressant effects

Abstract: Nonpeptidic delta-opioid receptor agonists produce antidepressant-like effects in rodents, and compounds that inhibit the breakdown of endogenous opioid peptides have antidepressant-like effects in animal models. In this study, the behavioral effects of the enkephalinase inhibitor, RB101 (N-[(R, S)-2-benzyl-3-[(S)(2-amino-4-methyl-thio)-butyldithio]-1-oxopropyl]-l-phenylalaninebenzyl ester), were examined. Specifically, the effects of RB101 on convulsive activity, locomotor activity, and antidepressant-like ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 27 publications
3
21
0
1
Order By: Relevance
“…One possible explanation could originate from the reported specific up-regulation of delta receptors in limbic structures of Penk1−/− mice (Clarke et al 2003b). This hypothesis is in agreement with previous studies, showing clearly that the antidepressant-like effects observed after RB101 administration were related to stimulation of delta opioid receptors by the endogenous enkephalins protected from their enzymatic degradation (Baamonde et al 1992;Jutkiewicz et al 2006;Nieto et al 2005). Moreover, in a recent study, we have already demonstrated that the residual antidepressant-like effect of RB 101 in Penk1−/− mice was blocked by the delta opioid selective antagonist, naltrindole (Bilkei-Gorzo et al 2007).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…One possible explanation could originate from the reported specific up-regulation of delta receptors in limbic structures of Penk1−/− mice (Clarke et al 2003b). This hypothesis is in agreement with previous studies, showing clearly that the antidepressant-like effects observed after RB101 administration were related to stimulation of delta opioid receptors by the endogenous enkephalins protected from their enzymatic degradation (Baamonde et al 1992;Jutkiewicz et al 2006;Nieto et al 2005). Moreover, in a recent study, we have already demonstrated that the residual antidepressant-like effect of RB 101 in Penk1−/− mice was blocked by the delta opioid selective antagonist, naltrindole (Bilkei-Gorzo et al 2007).…”
Section: Discussionsupporting
confidence: 85%
“…The dual inhibitors of enkephalin catabolism have been previously reported to elicit antidepressant-like effects in several animal models (Baamonde et al 1992;Jutkiewicz et al 2006;Nieto et al 2005;Tejedor-Real et al 1998). As expected, in the forced swim test, RB101 induced a highly significant decrease in the immobility time in wild-type mice, whereas a slight and plateauing reduction in immobility time was observed for the highest doses of the dual inhibitor in Penk1−/− animals (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…In several studies, the opioid receptors were proposed as a novel target system for the treatment of depression and anxiety (Nieto et al, 2005;Jutkiewicz et al, 2006;Saitoh et al, 2008). Opioid receptors are a family of G protein-coupled receptors and are classified as ␦, , and receptors, according to the endogenous opioid peptides, namely the endorphins, enkephalins, and dynorphin, respectively (Raynor et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…La raison a été discutée plus haut, et les références aux expériences qui le démontrent peuvent être trouvées dans différentes revues [13,17,19]. De même, l'effet antidépres-seur qui joue probablement sur la composante émotionnelle de la douleur trouve sa justification dans l'activation centrale des récepteurs delta [1,7]. L'absence de tolérance par rapport à la morphine est due à la différence dans le trafic des récepteurs stimulés par les enképhalines ou la morphine.…”
Section: Debio 0827 Et Douleur Neurophatiqueunclassified